Chemoradiotherapy effcacy in squamous cell rectal cancer: a propensity score matched analysis - V. V. Murzo; S. S. Gordeev; V. S. Myshlyakov; Z. Z. Mamedli (Сибирский онкологический журнал, 2023)
Introduction. Sporadic cases of squamous cell carcinoma of the rectum (rSCC) do not allow a comparative characterization of tumor aggressiveness and its response to chemoradiotherapy in relation to more common squamous cell entities, in particular, anal squamous cell carcinoma (aSCC). Objective: comparative evaluation of the short- and long-term results of chemoradiation therapy in patients with rSCC and aSCC. Material and Methods. In this retrospective study we included patients with nonmetastatic squamous cell carcinoma of the rectum (rSCC) and anal canal squamous cell carcinoma (aSCC) who received chemoradiotherapy and compared them in a 1:1 ratio using propensity-score matching. The dynamics of tumor response to treatment were compared by Kaplan-Meier survival analysis (OS and RFS) followed by Log-Rank verifcation, rate of complete response after 6 months. Results. A total of 15 pairs of matched patients were evaluated. Patients in both groups had reliably similar sex, age, histological grade, initial primary tumor size, differing only in tumor histological subtype. In the aSCC group, 60 % of patients had metastases to pelvic lymph nodes, while in the rSCC group metastases had 46.67 % (p=1). The median follow-up was 44 months. The 3-year OS in the aSCC group of patients was 76.9 %, and 71.4 % in the rSCC group (p=0.567). The 3-year DFS in the aSCC group was 66.7 %, and in the rSCC group 34.7 % (p=0.406). The rate of achieving complete clinical response to CRT after 6 months was 86.7 % for the aSCC group and only 46.7 % for the rSCC group (p=0.05). Organ-saving treatment was achieved in 93.3 % of aSCC patients and 73.3 % of rSCC patients (p=0.33). Conclusion. Overall and recurrence-free survival rates were not signifcantly decreased for rSCC patients relative to aSCC patients. This indicates a similar course and prognosis in the two diseases, but rSCC is characterized by a signifcantly lower rate of complete response to treatment.